2011
DOI: 10.1186/1752-153x-5-53
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fermentation, drying, roasting and Dutch processing on flavan-3-ol stereochemistry in cacao beans and cocoa ingredients

Abstract: This paper reports a systematic study of the level of flavan-3-ol monomers during typical processing steps as cacao beans are dried, fermented and roasted and the results of Dutch-processing. Methods have been used that resolve the stereoisomers of epicatechin and catechin. In beans harvested from unripe and ripe cacao pods, we find only (-)-epicatechin and (+)-catechin with (-)-epicatechin being by far the predominant isomer. When beans are fermented there is a large loss of both (-)-epicatechin and (+)-catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 39 publications
2
59
0
3
Order By: Relevance
“…Some authors reported degradation of flavonoids and tannins (i.e., polymeric forms of flavanoids) as a result of drying treatments (Gu et al, 2004;Kofink et al, 2007;Hurst et al, 2011). Therefore, an optimum combination of drying time/temperature should be established for each product's polyphenolic profile to minimize the degradation of these bioactive compounds during the dehydration leading to recover phenolic compounds and derivatives (Ahmad-Qasem et al, 2013).…”
Section: Total Phenolic Flavonoid and Flavanol Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported degradation of flavonoids and tannins (i.e., polymeric forms of flavanoids) as a result of drying treatments (Gu et al, 2004;Kofink et al, 2007;Hurst et al, 2011). Therefore, an optimum combination of drying time/temperature should be established for each product's polyphenolic profile to minimize the degradation of these bioactive compounds during the dehydration leading to recover phenolic compounds and derivatives (Ahmad-Qasem et al, 2013).…”
Section: Total Phenolic Flavonoid and Flavanol Contentsmentioning
confidence: 99%
“…Except, for 80 °C temperature increased the initial content of these compounds. Some authors reported an increase in flavanols during drying process which could be induced by high temperature (Kofink et al, 2007;Hurst et al, 2011). Waste olive cake, in some cases, exceeds the content of several food flavanols, thus this waste could be a rich source of these bioactive compounds (Francene et al, 2003).…”
Section: Total Phenolic Flavonoid and Flavanol Contentsmentioning
confidence: 99%
“…During conventional thermal processing, polyphenols are readily degraded and/or become bound to polymer structures [15]. There are several reports in the literature that roasting of cocoa beans led to a decrease in total polyphenol and total flavonoid content [16,17]. The main factor responsible for the degradation of these compounds is high temperature and contact with oxygen during thermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols such as gallocatechin, epicatechin (Figure 2E), epigallocatechin, epigallocatechin gallate, marsupsine, and pterostilbene show an antidiabetic activity [83][84]. Some studies report that polyphenols reduce blood glucose [85].…”
Section: Phenolic Compoundsmentioning
confidence: 99%